2014
DOI: 10.1007/s10278-014-9713-0
|View full text |Cite
|
Sign up to set email alerts
|

Academic Portfolio in the Digital Era: Organizing and Maintaining a Portfolio Using Reference Managers

Abstract: The academic portfolio has become an integral part of the promotions process. Creating and maintaining an academic portfolio in paper-based or web-based formats can be a cumbersome and time-consuming task. In this article, we describe an alternative way to efficiently organize an academic portfolio using a reference manager software, and discuss some of the afforded advantages. The reference manager software Papers (Mekentosj, Amsterdam, The Netherlands) was used to create an academic portfolio. The article ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…However, this feature supports the classical database and organization of knowledge as well as improve metadata searching performance [20], [21]. Besides, this feature also is an academic portfolio in the digitalization era [22].…”
Section: Resultsmentioning
confidence: 99%
“…However, this feature supports the classical database and organization of knowledge as well as improve metadata searching performance [20], [21]. Besides, this feature also is an academic portfolio in the digitalization era [22].…”
Section: Resultsmentioning
confidence: 99%
“…The need to expand the scope of a literature search to include additional disciplines in academia was also stated by Green et al [5] Medicine, radiology, midwifery, pharmacy, and dentistry are healthcare disciplines that utilize academic portfolios to track student development and competency attainment. [7][8][9][10][11] A supportive stance for the use of e-portfolios was common with comments such as "an integrative e-Portfolio experience can help students link and make meaning from various learning experiences" [12] and "findings indicated that learning portfolio practice can enhance the nature of the learning experience by providing students with a personal space to evaluate their own learning, to process their thoughts and experience and to document their lives and learning in an authentic and meaningful way". [13] Similar to the skills nurses need to develop, pharmaceutical standards require demonstration of "problem solving, educating different audiences, patient advocacy, interprofessional collaboration, cultural sensitivity, communication, leadership, innovation/entrepreneurship, and professionalism" which Daugherty and Cumberland propose are best suited for expression "via reflective portfolios".…”
Section: Describe Relevant Scholarshipmentioning
confidence: 99%
“…[13] Similar to the skills nurses need to develop, pharmaceutical standards require demonstration of "problem solving, educating different audiences, patient advocacy, interprofessional collaboration, cultural sensitivity, communication, leadership, innovation/entrepreneurship, and professionalism" which Daugherty and Cumberland propose are best suited for expression "via reflective portfolios". [11] 1.3.1 Benefits of academic portfolios Bhargava et al [7] spoke to an increased utilization of portfolios in both academic and employment settings. Gadbury-Amyot et al [9] saw a positive correlation between student portfolio quality and grade point average among dental hygiene students.…”
Section: Describe Relevant Scholarshipmentioning
confidence: 99%
“…Furthermore, this research also showed many Mendeley users were rather qualified to import papers either from desktop or website. The synchronization between desktop and web makes scholars tend to use Mendeley and other such reference manager to import documents for academic portfolio purpose [18]. Some of the papers on my Mendeley account are sourced directly from the journal website.…”
Section: P8mentioning
confidence: 99%